Pelaksanaan Pembelajaran Kewirausahaan untuk Pengembangan Usaha Jasa Penitipan Anak di SMK Negeri 13 Sarolangun - Khomsun, Imam (Universitas Batanghari Jambi, 2022)
SMKN 13 Sarolangun, Vocational School for Health and Social Work have had a very representative child care room to do child care business. One building with a size of 15 x 9 meters consisting of an air-conditioned play area with an area of 9 x 9 meters equipped with complete children's play equipment, one bedroom with an area of 6 x 4.5 meters, and a breastfeeding room with an area of 6 x 4.5 meters. HR available are 2 people with education background D-IV midwifery, 3 people with educational background S-1 Nursing. However Human resources and infrastructure at schools are actually adequate, not yet utilized well. Entrepreneurship learning at schools has not been implemented optimally. Learning process is still only a theory and has not been implemented in activities that can encourage the formation of entrepreneurial character in students. Learning entrepreneurship has not been integrated with vocational learning. Creative Product and Entrepreneurship Learning at Vocational High Schools must be integrated with vocational lessons. The internalization of entrepreneurial values at vocational learning becomes very important to raise the awareness of students and the formation of entrepreneurial character and habituation of entrepreneurial values into the daily behavior of students through the learning process. The growth of entrepreneurial character for students must be supported by activities related to the development of business units at schools. The business unit at school is an activity effort at schools and businesslike by utilizing all empowering resources owned by the school and managed professionally. This business activity can be done continually and expected to produce products and services which make benefits, namely by opening a Child Care Service (Daycare). Daycare activities at SMK Negeri 13 Sarolangun are done by Teaching Factory (TeFa). TeFa is a production facility which is operated based on real procedure and standard working to produce products/services in real conditions in Industry and Workplace (IDUKA). TeFa SMK is defined as â€œa learning concept in production at SMK based product (goods/services) which refers to standards and procedures that apply at IDUKA and implemented in an IDUKA environmentâ€, the implementation needs a partnership IDUKA. This activity is integrated with learning, especially entrepreneurship and vocational subjects, in particular the Healthcare Skills Programme. As a result, the implementation of production-based learning based on the TeFa model, the atmosphere of the Vocational School will change, not only the environment like in IDUKA, but the school's ecosystem and atmosphere must also change like the situation in IDUKA. Besides learning activities, schools will be busy with studentâ€™s activities by doing services toward society that is the basic principle of learning the TeFa model. To maximize more information about Daycare activities at SMK Negeri 13 Sarolangun Promotion is done through social media, such as Facebook, Instagram, YouTube, and others. Choosing social media because its reach wider range, very familiar to potential customers, and low cost. Thus, the implementation of Entrepreneurship learning can be more effective by doing direct activities, the development of child care services at SMKN 13 Sarolangun. In addition, learning can also give experience that the use of Social media as a promotion media gives experiences for students, especially related to how to promote product and service.